Learning in multicultural contexts without compromising quality and equivalence to balance local and global criteria - Pedigo, Kerry; Bolt, Susan (IADIS Press, 2012)
Curtin Business School (CBS) was one of the pioneer institutions to engage in international delivery of higher education in the Australasian region. CBS has over twenty years of experience in transnational education, with three branch campuses in Sarawak, Sydney and Singapore, as well as multiple twinning partnerships in Hong Kong, Malaysia, China, Indonesia and Mauritius. This paper presents the findings of a study which investigated this induction initiative undertaken by CBS under the leadership of the authors in 2011-12. This initiative involved improving induction processes and support in the transnational teaching context of CBS with the aim of ensuring students across diverse contexts and locations were provided with comparable quality teaching and learning experiences. As a result several resources including a USB which contained a film and other resources were developed. In this project the researchers sought feedback from participants related to the usefulness of the resources and suggestions for improvement. This study investigated the validity of an induction package and focusing on inducting casual teaching staff in local and transnational teaching contexts.